Processing Coffee Grounds Waste as a Planting Media in the Use of Organic Fertilizer in Pabedilan Wetan Village, Cirebon Regency - Aliet Noorhayati Sutisno; Dewiantika Azizah; Noor Novianawanti; Dewi Nurdiyanti (Ann Publisher, 2023)
So far, the increase in coffee bean utilization is not directly proportional to itsenvironmental impact. The benefits of coffee beans for health should align with how coffeewaste is also valuable in strengthening the community's economy. Educational steps areneeded for coffee cafes as waste producers. As university personnel, we should mediate thisgap. Community service activities are carried out at QQ café as part of a coffee wasteprogram to be used by farmer groups (POKTAN) Mrengkel I, Pabedilan District, CirebonRegency. This community service activity aims to educate the public how coffee wasteproduced routinely by QQ café as much as 4-5 kg in a week, can be absorbed by theMrengkel I group, Pabedilan District, Cirebon Regency as a party who needs coffee wasteas an alternative to organic fertilizer. Service activities are carried out for four months. Theresults showed that waste management started with sorting techniques on the part of coffeewaste producers for four months, continued at the fermentation step of waste that wassuccessfully collected in a particular vessel, and then ended with waste being handed overto the farming community along with a book on the use of coffee grounds to be used as analternative to organic fertilizer at least succeeded in educating and mediating one party tothe other. That way, the community service activities that we carry out are a form ofdissemination of our research results in educating the public while developing science andtechnology.